Management of the Company’s Investment Projects in Anti-Crisis Management and Their Impact on the Environment - ALASHBAIEVA, Nursulu; TUREKULOVA, Dametken; KAPENOVA, Asemgul; ZHUNUSOVA, Aliya; SUTBAYEVA, Raikhan (Journal of Environmental Management and Tourism, 2021)
Neglect of social and environmental aspects can lead and, unfortunately, does lead to unplanned risks, the damage from which can significantly affect the economic component of the project, and in critical situations even reduce the feasibility and the very possibility of project implementation to zero. That is why, at all stages of work in the framework of a newly created or already existing investment project, it is necessary to pay close attention to the study of the widest range of social and environmental aspects and their impact on its economic component. Therefore, the role of anti-crisis management in the management and development of the organization is very important, as it affects all indicators of the enterprise's development, optimizing them.